Bioluminescent Microalgae-Based Biosensor for Metal Detection in Water - Wong, Ling Shing*; Simranjeet, Kaur Judge; Wan, Betty Voon Niu; Lee, Jia Tee; Ka, Yee Tan; Megalah, Murti; Mee, Kin Chai (IEEE, 2018)
Anthropogenic activities cause serious metal pollution, and thus an effective screening method is important to indicate the presence of these pollutants in water. In this paper, a biosensor was developed to detect the presence of both heavy metals (Cu, Pb, and Cd) and light metals (Na, Al, and Li) in water. Microalgae chlorella vulgaris was used as the biological component, and the bioluminescence response of the microalgae to the metals was utilized as indication parameter (with λ = 350 - 650 nm). The effects of pH, age of cell culture, and the density of the cells to the bioluminescence response were studied. From the experiment, the presence of these metals with the concentrations of 0.001 - 10.000 nm/L could be detected rapidly within 15 min of exposure. The usage of broad spectrum luminescence as indicator made the biosensor more cost effective. The sensitivity of the algae cells to the various environmental pollutants enabled the biosensor to respond to a wide range of metals within a short-period of exposure time. Furthermore, using non-genetically modified algae as biological component eluded strict regulations on the usage of genetic modified microbe in the field.